Progress in programmatic management of drug-resistant TB, WHO Eastern Mediterranean Region, 2018-2023 - K. Bennani; M. van den Boom; M.G. ElMedrek; Y. Hutin (IJTLD Open)
BACKGROUND: Since 2012, WHO has supported countries in scaling up programmatic management of drug-resistant tuberculosis (PMDT). We assessed progress and challenges to formulate recommendations for improvement. METHODS: We reviewed the regional Green Light Committee (rGLC)mission reports and analysed data to describe the progression of programme indicators. RESULTS: The proportion of TB patients initially tested using Xpert MTB/RIF rose from 5% in 2017 to 54% in 2022. Testing for rifampicin-resistant TB (RR-TB) increased from 4% in 2015 to 68% in 2022 among new patients and from 17% in 2015 to 94% in 2022 among those previously treated. Consequently, in 2021–2022, the number of multidrug-resistant (MDR)/RR-TB patients diagnosed increased by 29% and 84% of them were treated, accounting for 22% of estimated cases. By 2023, fourteen countries had implemented all-oral regimens, with three initiating the 6-month bedaquiline, pretomanid, linezolid, and moxifloxacin regimen (BPaL(M)). MDR/RR-TB treatment success increased from 64% in 2017 to 73% in 2020. CONCLUSIONS: Eastern Mediterranean Region countries progressed in PMDT using Xpert MTB/RIF, increased diagnosis and treatment of MDR/RR-TB patients using all-oral regimens, and improved treatment success. They must now enhance diagnostic capacity using WHO-recommended diagnostics, decentralise services while integrating them into primary health care, and prioritise the BPaL(M) regimen.